STUDIUL INDIVIDUAL AL STUDENTULUI: PARCURS EVOLUTIV - USM ADMIN (Moldova State University, 2012)
This article approaches the individual study of student as a way the method for the formation of professional skills. There are appointed types, forms and levels of individual study, also stylistic profiles of manifestation in educational environment. It follows the evolution of student independence reporting to learning activities from external control to self-control and self-monitoring of independent work. There is proposed the demarche of elaboration a complex individual study, step by step.